Analisis Jaminan Produk Halal Menggunakan Sertifikasi Halal dalam Meningkatkan Daya Saing : (Studi pada Produk Pisang Sale di Desa Purwo Bakti Kecamatan Bathin III) - Fika Nadila; Muhammad Ismail; Agustina Mutia (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Halal food halal refers to good food that does not contain substances or ingredients that are dangerous or prohibited in Islamic teachings and are prohibited from being eaten by Muslims. According to Islamic economics, halal certification is used to determine the halalness of a product being sold. This research aims to find out how the implementation of the halal guarantee system can increase competitiveness. Judging from the research objectives, this research uses qualitative methods by combining observation, interview and documentary data collection techniques. Research data regarding halal product guarantees for halal food products in Purwo Bakti Village, Bathin III Bungo District is in-depth and comprehensive. Then data acquisition was carried out and descriptive analysis was carried out. The research results show that the implementation of the Halal Guarantee System (SJH) using halal certification by business owners, the implementation components are materials, products, product facilities, traceability and product handling that meet the criteria. Pisang Sale has halal certification which is shown by the presence of a halal certificate and other factors so that business people think that having a halal label on the product packaging makes buyers more confident in buying and makes it easier to market the product in supermarkets and nearby shops.